ПРЕЗИДЕНТ ШАВКАТ МИРЗИЁЕВ – МИЛЛЕТЛЕРАРА ҲӘМ ДИНЛЕРАРА ТАТЫЎЛЫҚ ҲАҚҚЫНДА - Абаев, С.; Якубов, М.; Сарыбаев, М. (ILIM hám JÁMIYET, 2024)
The article deals with the notion of ideas international agreement and religious tolerance on the basis of works of President Sh.Mirziyoyev.